The origin of decoupled Hf-Nd isotope compositions in Eoarchean rocks from southern West Greenland - Hoffmann, J. Elis; Muenker, Carsten; Polat, Ali; Rosing, Minik T.; Schulz, Toni (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Radiogenic isotope compositions of Hf and Nd are typically coupled in Phanerozoic and Proterozoic mafic rocks due to a similar behaviour of Lu-Hf and Sm-Nd during mantle melting. Eoarchean rocks, for instance those from southern West Greenland, exhibit an apparent decoupling of Hf and Nd isotope compositions. This apparent decoupling may either indicate metamorphic disturbance or, alternatively, mirror early differentiation processes in the silicate Earth. To evaluate the issue, we performed combined measurements of Hf-Nd isotope compositions together with major and trace element concentrations for well preserved >3720 to >3800 Ma old tholeiitic metabasalts and gabbros from the similar to 3700 Ma and similar to 3800 Ma old terranes of the Isua Supracrustal Belt, southern West Greenland. In contrast to younger mafic rocks, calculated initial epsilon Hf-epsilon Nd values of the Isua tholeiites show similar spreads and are both near chondritic to strongly depleted (-0.7 to +6.3 and -0.8 to +4.4, respectively), also in contrast to previously reported more depleted signatures in nearby boninite-like metabasalts of the Garbenschiefer unit. An evaluation of alteration effects based on preserved major and trace element arrays reveals pristine magmatic trends and therefore the measured isotope compositions indeed in most cases characterize contrasting Eoarchean mantle sources. In accord with this view, compositions of the Isua metabasalts yield Eoarchean regression ages in Sm-Nd and Lu-Hf isochron spaces, overlapping with emplacement ages inferred from crosscutting relationships with tonalites. Lutetium-Hf systematics of the Isua metabasalts studied here, yield clear isochron relationships. For both terranes, there is some scatter in Sm-Nd space, indicating early disturbance of the Sm-Nd system close in time to the extrusion ages, possibly by seafloor alteration. Trace element compositions of the metabasalts indicate an arc setting and a strong source overprint by melt-like subduction components. It is likely, that ...